THE EXTENT OF MEDICINE WASTAGES IN A TERTIARY HOSPITAL IN BRUNEI: 10 YEARS’ RETROSPECTIVE STUDY FROM 2006 TO 2016 - Kifli, Nurolaini; Wai See, Wong; Chaw, Li Ling (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Access to health and medical care for Bruneians is at a negligible cost. Medication wastage poses a financial burden on the nation’s economy. This retrospective study aims to measure the extent of medicines wastage in a tertiary hospital in Brunei Darussalam and its relation to the costs. Methods: The collected dataset records all information on returned medicines to the inpatient pharmacy in Raja Isteri Pengiran Anak Saleha hospital from 2006 to 2016. This information includes the dates and location from where medication is returned, its form, its unit price, and its status after being returned. The datum was analyzed using R statistical software (version 3.3). Results: A total of 1,290,254 units of medications were returned, totaling BND 3,703,170. These medications were returned from hospital wards (88.5%), inpatient pharmacy (34.3%), and health centers (2.7%). The majority of returned medications were in an oral solid form (78.5%), followed by injections (13.7%) and topical preparations (3.2%). Among the recorded medications, 53.8% were eventually reused (a total of BND 1,177,147) and 38.3% were disposed (a total of BND 1,538,022). Oral solids formed the majority of both the reused (89.7%) and disposed (74.7%) medications. 60.2% of the medications returned by the hospital wards were reused. Conclusion: Medication recycling and wastage exist in Brunei. Health-care policymakers should be informed to implement wastage reduction strategies. One major limitation is the amount of missing data and the consistency of data entry. The eventual destinations of 7.8% of the returned medications were unrecorded and 879 entries (1.4%) were removed from the analysis, after applying the exclusion criteria and also to account for suspected data entry errors.